Sistem Pakar Pasal-Pasal Pidana Penghapusan Kekerasan dalam Rumah Tangga dengan Metode Forward Chaining - Yumarlin MZ; Sri Rahayu (Universitas Hamzanwadi, 2023)
Domestic and Family Violence (DFV) is a social issue that often occurs in Indonesia, especially for women. Domestic violence cases often cannot be handled thoroughly because legal issues are very complex, making it difficult for ordinary people to understand and sort out the articles that regulate a legal case in domestic violence. This research aims to produce an expert system that can make it easier for the public to find solutions in the form of articles suspected of being involved in a crime of domestic violence. An expert system built with the stages of analysis, design, implementation, and testing. The analysis phase was carried out by observation and interviews or discussions with staff from the District Attorney's Office for the Sleman Regency, Special Region of Yogyakarta. The implementation phase uses the Forward Chaining inference technique to produce the basic rules for determining the articles suspected of acts of violence committed. System testing using SUPR-Q involved 30 respondents to fill out questionnaires from 3 aspects of user experience namely usability, user interface, and satisfaction. The test results obtained a percentage of 80.66% indicating a very good level of ease and satisfaction of the expert system for eliminating domestic violence.